PROPORSIONALITAS WARTAWAN TELEVISI LOKAL DI BATU TV - Aryo Prakoso Wibowo (Jurnal Nomosleca, 2018)
Abstract This study aims to determine the extent to which the professionalism of TV journalists to process information to become a debate of opinion for the local community about local phenomena. The process of producing news is important to provide good news content to the public. The good news is presented by journalists who understand and adhere to the journalist's code of ethics. Because journalists are professionals who work based on rules or code of ethics journalism as an operational handle to maintain public confidence, uphold integrity and professionalism. The performance of journalists must uphold the code of ethics of television journalists, among other things "not to engineer events, images or sounds to be made news" (article 5 point c) and then in chapter 10 point c reads "as distinguish between the facts and opinions, . It relies heavily on the quality of human resources of television journalists to produce quality news. The results obtained in the study show that Journalists at Batu TV are not "free" individuals who produce truth through journalistic outcomes, but rather because of the demands of corporate capitalism. Batu TV prioritizes Profit Oriented so that the news is dominated by order news (blockingtime). Under these circumstances, journalists are faced with a dilemma between a pure report in the journalist's code of ethics with news of orders being polished for commercial demands. Keywords: Code of Ethics Journalism, News, Local Journalists DOI : https://doi.org/10.26905/nomosleca.v4i1.2073